2004
DOI: 10.1212/01.wnl.0000110311.09970.83
|View full text |Cite
|
Sign up to set email alerts
|

Early risk of recurrence by subtype of ischemic stroke in population-based incidence studies

Abstract: The risk of early recurrent stroke is highest in patients with LAA. This supports the need for urgent carotid imaging and prompt endarterectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
404
4
25

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 685 publications
(457 citation statements)
references
References 21 publications
24
404
4
25
Order By: Relevance
“…Large artery atherosclerosis had the highest risk of 30‐day recurrence in our study, as previously reported by other studies (Lovett et al, 2004; Petty et al, 2000; Sacco, 1997). Considering that CEA is highly effective for reducing recurrent stroke in selected patients with stenosis of the internal carotid artery (Rothwell et al, 2003), knowing the risk of early recurrence is important for the stroke clinician in order to select and time patients for surgery.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Large artery atherosclerosis had the highest risk of 30‐day recurrence in our study, as previously reported by other studies (Lovett et al, 2004; Petty et al, 2000; Sacco, 1997). Considering that CEA is highly effective for reducing recurrent stroke in selected patients with stenosis of the internal carotid artery (Rothwell et al, 2003), knowing the risk of early recurrence is important for the stroke clinician in order to select and time patients for surgery.…”
Section: Discussionsupporting
confidence: 91%
“…There is scant information on stroke recurrence in Norway, but our rate is low compared to many large international incidence studies (Bravata, Ho, Meehan, Brass, & Concato, 2007; Lovett et al, 2004; Sacco et al, 1994; Smith, Frytak, Liou, & Finch, 2005). Most of these studies included patients dating several decades back.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Recurrent risk is associated with the underlying stroke etiology [9][10][11]. The estimated risk of stroke recurrence is 10 to 20% within the first 3 months.…”
Section: Clinical Trials For Prevention Of Early Stroke Recurrencesmentioning
confidence: 99%